2017
DOI: 10.1038/ncomms15276
|View full text |Cite
|
Sign up to set email alerts
|

Time-compressed preplay of anticipated events in human primary visual cortex

Abstract: Perception is guided by the anticipation of future events. It has been hypothesized that this process may be implemented by pattern completion in early visual cortex, in which a stimulus sequence is recreated after only a subset of the visual input is provided. Here we test this hypothesis using ultra-fast functional magnetic resonance imaging to measure BOLD activity at precisely defined receptive field locations in visual cortex (V1) of human volunteers. We find that after familiarizing subjects with a spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
171
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(209 citation statements)
references
References 50 publications
32
171
6
Order By: Relevance
“…For example, while both macaque V1 and V2 neurons respond to the illusory contour of a Kanizsa triangle, V2 neurons consistently respond earlier than those in V1 130 . Several fMRI studies have also reported that patterns of neural activity evoked in early visual cortex following the omission of an expected stimulus resemble the activity evoked by the veridical stimulus 49,51,132 and this result has been replicated in recordings from rodent V1 52 . Muckli et al 132 .…”
Section: Hypothesis 2: Top‐down Signals Represent Sensory Predictionsmentioning
confidence: 90%
See 3 more Smart Citations
“…For example, while both macaque V1 and V2 neurons respond to the illusory contour of a Kanizsa triangle, V2 neurons consistently respond earlier than those in V1 130 . Several fMRI studies have also reported that patterns of neural activity evoked in early visual cortex following the omission of an expected stimulus resemble the activity evoked by the veridical stimulus 49,51,132 and this result has been replicated in recordings from rodent V1 52 . Muckli et al 132 .…”
Section: Hypothesis 2: Top‐down Signals Represent Sensory Predictionsmentioning
confidence: 90%
“…Interestingly, the activity was present up to 600 ms after stimulus offset and was temporarily erased by the presence of a visual mask, but reinstated on mask removal, demonstrating that the activity could not be explained through iconic memory mechanisms 133 . In a human fMRI study, Ekman et al 51 . repeatedly exposed participants to a dot stimulus rapidly moving across a screen.…”
Section: Hypothesis 2: Top‐down Signals Represent Sensory Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent 57 studies indicate that pRF size and eccentricity vary in concert when the task requires to move the 58 focus of attention from fixation to the mapping stimulus, suggesting that processing resources are 59 Specifically, the position of a coherently moving stimulus can be anticipated based on its current 75 location and the direction of motion. The predictability of the stimulus location could induce an 76 anticipatory response in such locations (Ekman, Kok, & de Lange, 2017). Moreover, knowledge 77 of the upcoming stimulus location can provide spatial cues to direct attention to the relevant portion 78 of the screen affecting pRF estimates accordingly (Kastner, Pinsk, De Weerd, Desimone, & 79 Ungerleider, 1999).…”
mentioning
confidence: 99%